A study of Time-Of-Flight applications using a TOF camera sensor board - Muhamad Alif Bin Mohd Jaffery (2023)
ABSTRACT Range sensing cameras are often used to obtained depth information similarly on how bats sense its surroundings. The most common principle used to achieve depth information is structured-light. However, the time-of-flight principle, which uses the distance obtained by calculating the reflected light emitted by the sensor onto the object. The time-of-flight principle is much more efficient and simpler, requiring less processing power to achieve its goal compared to its other alternatives such as structured-light as we can see from both generations of the Kinect developed by Microsoft. In this project, the People Tracking and Counting application is used to simulate the workings of the time-of-flight principle using a ToF camera sensor board and a Raspberry Pi 2B. Different resolutions were tested to obtain the performance differences of the ToF sensor. Higher resolution provided more detail picture of the scenery at the cost of low framerates. The accuracy of the People Tracking and Counting application was mainly dependent on the environment of the scenery. Modifications of the camera parameters were required to increase the accuracy of the tracking algorithm depending on the scenery. Multiple scenes were tested in this project.